The Word of Islam - Riad Nourallah (International Institute of Islamic Thought, 1994)
Anthologies have been known to string together mangled pieces of writing in ways reminiscent of a tanner's drying rack or a horror film studio's collection of gory rubber limbs and masks. But there seems to be little disparity, disjunction, or morbidity in Professor Williams's book, his second major attempt to "let Islam speak for itself." The first was the seminal Islam, which came out in 1961 and broke new ground as well as a few fetters. The new endeavor sets out to offer the faith (and the culture associated with it) a better-tuned mike at a time when the dominant world media is busy blackening its name and reputation. Of course, even with the best of intentions, the task of introducing Islam in capsule form, its own essential simplicity notwithstanding, is both impossible and unfair. The editor, however, is alive to the predicament and recognizes that Islam, like "every great religion," is akin to an "ocean, with many bays, inlets, and unplumbed areas." In essence, "we can only come to it, smell it, taste it, touch it, observe what thrives there, and listen to its many moods." The sentiment may betray an outsider's perspective, but it is refreshingly honest and respectful. Moreover, it is the product of a long engagement with and pondering over such pedagogic issues as "how one may most effectively and practically study Islam." No short-cut, not even a good anthology, is recommended. Rather, read the texts which convey its tradition in as wide a range as one can. An original text is worth more than many words of explanation. Go to the sources and listen to voices that have rung with authority for generations, that Muslims have recognized, and use only enough introductory material to set the voice in its context. Some may argue whether presenting translated extracts from the basic Islamic canon to a modern and arguably hostile or misinformed audience requires ample commentary. But the editor, in addition to his main concern of presenting that canon in meaningful digest form, takes care to demarcate the territory between ancient and modem. Be that as it may, to a large degree he succeeds in choosing (and translating) highly pertinent and interrelated excerpts as well as in introducing them with conciseness and clarity, erudition and sympathy ...